Blueprints for reform (Oxford University Press, 1998)
Blueprints for Reform includes discussions of equity, assessment, teacher education, policy, finance, school organization, curriculum connections, family and community, research, materials and technology, and business and industry. A chapter is devoted to each of these topics providing an overview of the issue and some recommendations on how to move forward. The idea behind this strategy is to bring current research together in one place so anyone working in the area of science education and reform can have complete access to the latest information, methods, and debates